About the Experience in the Implementation of Joint Educational Programs at the Ural Federal University - Vostretsova, Elena Vladimirovna; Ignatchenko, Olga Arkadievna; Satybaldina, Elena Vladimirovna (International Review of Management and Marketing, 2016)
The priority activities of the Ural Federal University and integration into the international and domestic educational environment, in particular, are described. The experience of the University in the development and implementation of joint educational programs and their value to the University, which is the main supplier of highly qualified personnel at the regional scale, are considered. The necessity of creation of internal regulatory system of the University, regulating all aspects of interaction between the partner universities in the process of development and implementation of joint educational programs, is grounded. The main trends and educational interaction partners, as well as the basic conditions for the implementation of this type of programs, such as distance learning technologies and electronic educational resources, are described. The main problems, arising in the implementation of joint programs, as well as their solutions, are described. Keywords: joint educational program, internationalization of educational activity, international educational environment JEL Classifications: I230, I280, I210